In vitro Effects of Lemongrass Extract on Candida albicans Biofilms, Human Cells Viability, and Denture Surface - Madeira, Petrus L. B.; Carvalho, Letícia T.; Paschoal, Marco A. B.; de Sousa, Eduardo M.; Moffa, Eduardo B.; da Silva, Marcos A. dos Santos; Tavarez, Rudys de Jesus Rodolfo; Gonçalves, Letícia M. (Frontiers in Cellular and Infection Microbiology, 2016)
The purpose of this study was to investigate whether immersion of a denture surface in lemongrass extract (LGE) has effects on C. albicans biofilms, human cell viability and denture surface. Minimal inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) were performed for LGE against C. albicans. For biofilm analysis, discs were fabricated using a denture acrylic resin with surface roughness standardization. C. albicans biofilms were developed on saliva-coated discs, and the effects of LGE at MIC, 5XMIC, and 10XMIC were investigated during biofilm formation and after biofilm maturation. Biofilms were investigated for cell counting, metabolic activity, and microscopic analysis. The cytotoxicity of different concentrations of LGE to peripheral blood mononuclear cells (PBMC) was analyzed using MTT. The effects of LGE on acrylic resin were verified by measuring changes in roughness, color and flexural strength after 28 days of immersion. Data were analyzed by ANOVA, followed by a Tukey test at a 5% significance level. The minimal concentration of LGE required to inhibit C. albicans growth was 0.625 mg/mL, while MFC was 2.5 mg/mL. The presence of LGE during biofilm development resulted in a reduction of cell counting (p < 0.05), which made the MIC sufficient to reduce approximately 90% of cells (p < 0.0001). The exposure of LGE after biofilm maturation also had a significant antifungal effect at all concentrations (p < 0.05). When compared to the control group, the exposure of PBMC to LGE at MIC resulted in similar viability (p > 0.05). There were no verified differences in color perception, roughness, or flexural strength after immersion in LGE at MIC compared to the control (p > 0.05). It could be concluded that immersion of the denture surface in LGE was effective in reducing C. albicans biofilms with no deleterious effects on acrylic properties at MIC. MIC was also an effective and safe concentration for use.